Aplikasi Pendaftaran Siswa Berbasis Web Sebagai Solusi Penerimaan Siswa Baru di MAN Darussalam Aceh Besar - Akbar, M.; Hajriyanti, Rahmi; Ismail (Computer Journal, 2025)
This study develops a web-based student registration application to overcome problems in the new student admission process at MAN Darussalam Aceh Besar. The manual system that was previously implemented caused various obstacles such as data recording errors, difficulty in finding information, and the length of the data processing process. Using the waterfall method, this study conducted a needs analysis through interviews, observations, and documentation studies, followed by system design using ERD and the MVC approach. Implementation was carried out using the programming languages HTML, CSS, JavaScript, PHP, and MySQL as the database. System testing was carried out in stages through unit testing, integration, system testing, and user acceptance. The results of the study showed that the application successfully provided an efficient, accurate, and easily accessible online registration platform, with integrated data validation features, prospective student data management, selection process, result announcements, and report generation. This application has proven effective in improving the quality of new student registration services at MAN Darussalam Aceh Besar